PROPERTIES OF QUINOXALINE OXIDE-RESISTANT RICKETTSIA TYPHI - Weiss, Emilio (1962)
Weiss, Emilio (Naval Medical Research Institute, Bethesda, Md.) and Harry R. Dressler. Properties of quinoxaline oxide-resistant Rickettsia typhi. J. Bacteriol. 83:415–417. 1962.—An effort was made to apply to the Wilmington strain of Rickettsia typhi the observation that in certain strains of rickettsiae and viruses of the psittacosis group quinoxaline oxide resistance is easily obtained and is often accompanied by other changes. Resistance to quinoxaline oxide was obtained in R. typhi after 14 serial egg passages by a procedure somewhat more elaborate than the one used previously for R. prowazekii. Three limit-dilution isolates manifested an appreciable level of drug resistance (were unaffected by 0.5 mg/egg), but changes for unselected characteristics, such as “toxicity” for the mouse or growth or virulence for the chick embryo, were small and different in each case, and did not clearly resemble those obtained with the other microorganisms.